2013
DOI: 10.1177/1934578x1300800710
|View full text |Cite
|
Sign up to set email alerts
|

Formal Synthesis of (+)-Madindoline A a Potent IL-6 Inhibitor Utilizing Enzymatic Discrimination of Quaternary Carbon

Abstract: A formal synthesis of (+)-madindoline A was achieved. The Sunazuka's key intermediate (4 R,5 S)-(–)-3-butyl-4-( tert-butyldimethylsiloxy)-5-methoxycarbonyl-2,5-dimethyl-2-cyclopentenone was synthesized from easily available (2 S,3 S)-3-acetoxy-2-ethenyl-2-methylcyclopentanone. The starting material was reliably supplied by a chemo-enzymatic procedure in enantiomerically pure form. The synthesis was performed by straightforward transformations involving enone formation and regioselective introduction of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Shimizu et al 37 successfully executed a formal synthesis of madindolines, commencing with acetoxycyclopentenone 85, achieved through inversion of the secondary alcohol, introduction of a carbon-carbon double bond, and a regioselective oxidative cleavage of the terminal vinyl group (Scheme 11). 37 In the outlined process, previously reported acetoxycyclopentenone 85 underwent acid-catalyzed hydrolysis to furnish alcohol 86. A Mitsunobu S C H E M E 9 Total synthesis of (+)-madindolines A (1) and B (2) by Wan et al 35 reaction, followed by methanolysis under basic conditions, provided the volatile secondary alcohol possessing the requisite stereochemistry at the C-3 carbon.…”
Section: Formal Synthesis By Shimizu Et Al (2013)mentioning
confidence: 99%
See 1 more Smart Citation
“…Shimizu et al 37 successfully executed a formal synthesis of madindolines, commencing with acetoxycyclopentenone 85, achieved through inversion of the secondary alcohol, introduction of a carbon-carbon double bond, and a regioselective oxidative cleavage of the terminal vinyl group (Scheme 11). 37 In the outlined process, previously reported acetoxycyclopentenone 85 underwent acid-catalyzed hydrolysis to furnish alcohol 86. A Mitsunobu S C H E M E 9 Total synthesis of (+)-madindolines A (1) and B (2) by Wan et al 35 reaction, followed by methanolysis under basic conditions, provided the volatile secondary alcohol possessing the requisite stereochemistry at the C-3 carbon.…”
Section: Formal Synthesis By Shimizu Et Al (2013)mentioning
confidence: 99%
“…Shimizu et al 37 successfully executed a formal synthesis of madindolines, commencing with acetoxycyclopentenone 85 , achieved through inversion of the secondary alcohol, introduction of a carbon‐carbon double bond, and a regioselective oxidative cleavage of the terminal vinyl group (Scheme 11). 37 In the outlined process, previously reported acetoxycyclopentenone 85 underwent acid‐catalyzed hydrolysis to furnish alcohol 86 . A Mitsunobu reaction, followed by methanolysis under basic conditions, provided the volatile secondary alcohol possessing the requisite stereochemistry at the C‐3 carbon.…”
Section: Madindolinesmentioning
confidence: 99%
“…Owing to the importance of (2S, 3S)−2,2-disubstituted-3-hydroxyketones, which could be used for the preparation of many natural products, such as cortistatin A, clavulactone, madindoline A, digitoxigenin and hygrophorone (Supplementary Fig. 8) [36][37][38][39][40][41] , enzyme kinetic parameters of CbAR towards 1e were then analyzed. It showed that its K m and k cat values were 5.13 ± 0.33 mM and 0.58 ± 0.01 min −1 (Supplementary Table 4), respectively, suggesting that the catalytic activity of CbAR towards 1e is much lower than that towards to 1a (Supplementary Fig.…”
Section: Molecular Insights Of Emodin Recognition and Binding Of Cbarmentioning
confidence: 99%
“…2,2-Disubstituted-3-hydroxycyclopentanones with two chiral centers are important chiral intermediates for the synthesis of natural products and drugs, such as bicyclo[9.3.0]­tetradecenone, (+)-digitoxigenin, (+)-madindoline A, (+)-estrone, and cortistatins (Figure A). (2 R ,3 R )-Ketol is the key chiral intermediate for the synthesis of (+)-estrone and cortistatins.…”
Section: Introductionmentioning
confidence: 99%